Implementation and Challenges of Solid Waste Management in Communities of a Component City in the Philippines - Gamao, Roldan; Caelian, Merlita (Technium Social Sciences Journal, 2023)
Waste management is a worldwide issue other than climate change and global warming. In the ASEAN, there is an extraordinary increase in solid waste traced to urbanization, industrial development, and economic growth. While the Philippines enacted the Ecological Solid Waste Management Act, local governments passed the Environment Code. This study determined the extent of implementation of the city ordinance on solid waste management of communities in terms of the variables assessed by a sample size of 67 implementers and 384 residents identified by stratified random sampling. It also investigated the challenges encountered by the respondents in the implementation. Likewise, the differences were determined according to the geographical location of coastal, upland, and lowlands and when respondents were grouped according to designation. Using descriptive analysis, the results revealed that, as a whole, implementation of the provisions of the city ordinance is, to a great extent, with waste generation as the highest while handling and on-site storage the lowest, but several challenges were encountered. The comparative analysis revealed no significant difference in the extent of implementation when respondents were grouped according to designation in all areas except waste disposal. However, there was a significant difference when communities were grouped by geographical location, with lowland residents rating higher than the rest. Three groups of challenges emerged from the study: administrative, procedural, and policy issues.